EVALUASI FORMULASI MASKER CLAY DARI EKSTRAK ETANOl DAUN PEPAYA (CARICA PAPAYA L.) SEBAGAI ANTI JERAWAT - Fauziah, Fauziah; Alvanny, Nurliza; Andalia, Kiki (Jurnal Riset Kefarmasian Indonesia, 2022)
Papaya Leaf Extract is known to contain alkaloid and flavonoid compounds that can inhibit the preparation of peptidoglycan in bacterial cells and reduce immunity in target organisms. For ease of use of papaya leaf extract, it is formulated in the form of a mask. This study aims to formulate a clay mask from papaya leaf ethanol extract and the effectiveness of anti-acne use of clay mask preparation of papaya leaf ethanol extract for 4 weeks. The method used in this study is an experimental method carried out at the AKAFARMA laboratory in Banda Aceh. The samples used were Formula 0, Formula 1, Formula 2 and Formula 3 masks of papaya leaf ethanol extract with concentrations for Formula 1 (2.5 %), Formula 2 (5%) and Formula 3 (7%). The results of the research on the physical properties and stability of the clay mask preparation on organoleptic testing showed that all formulas did not change color and odor for 4 weeks, but there was a change in shape at F0, FI, and FII on the 28th day. The homogeneity test of all preparations showed a homogeneous arrangement. The resulting pH test is 5.7-6.5, the resulting dispersion test is 5-5.5. The dried preparation test resulted in 25-30 minutes. and the anti-acne effectiveness test of each mask preparation F0, FI, FII, and FIII the average percentage reduction in the number of acne was 20.83%, 22.63%, 28.75%, and 50%. Papaya leaf ethanol extract clay mask FIII (7.5%) was the maximum in reducing the number of pimples on the volunteers' faces. The conclusion in this study is that papaya leaves can be formulated as a clay mask.